Teacher Guidance in Shaping Religious Character of Students: A Case Study at Vocational School - Husain, Ernawati; Usman, Syahruddin; U, Muhammad Shabir; Yahdi, Muhammad; Rahman, Danial (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study aims to analyze the role of teacher guidance in shaping the religious character of students at SMK (Vocational School) Televisi Watampone, Bone Regency. Employing a qualitative research method with a phenomenological approach, the subjects of this research include students, teachers, and the school principal. Data collection techniques encompass observation, interviews, and documentation, and the data were analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that teacher guidance significantly impacts students' character development. Initially, students exhibited poor character, but through consistent and focused guidance, their behaviors improved. The guidance emphasizes character development in relation to God, fellow human beings, and the environment. With patience and dedication, teachers at SMK Televisi Watampone have effectively nurtured their students' religious character. This study highlights the importance of aligning character development guidance with students' relationships with God, their peers, and their interaction with the environment. The significant behavioral transformation observed in students underscores the crucial role of teacher guidance in shaping religious character. Future research should explore the long-term effects of such guidance on students' overall personal and academic development and investigate the effectiveness of various approaches in fostering religious character within educational settings.